2015
DOI: 10.11648/j.ajim.20150304.16
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Dysfunction and Morphological Abnormalities in Patients with Type 1 Diabetes Mellitus

Abstract: Background: Type 1 diabetes mellitus is an autoimmune disease. Several studies have documented great variations in the prevalence of thyroid dysfunction and autoimmune thyroid disease (AITD) in type 1 diabetic patients. Undiagnosed thyroid dysfunction has negative impact on the metabolic control and will aggravate the cardiovascular disorders. Objectives: We aimed to investigate the presence of thyroid dysfunction and the associated morphological abnormalities in type 1 diabetes mellitus. Methods: 80 type 1 di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
1

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
0
1
Order By: Relevance
“…who reported 30.4%, Lee et al16 who reported 38.8%, Kang et al 17 who reported 28.8%, Jung et al18 who also reported 26% prevalence of AITD among T1DM patients and also with Perros et al19 who reported 31.4% as an incidence of thyroid dysfunction among T1DM female patients, but our results were lower than the study done by Heba et al20 , who found it 65%, while it is more higher than the study of Hansen et al 21 who found 5% of patients with T1DM had thyroid dysfunction.…”
contrasting
confidence: 60%
“…who reported 30.4%, Lee et al16 who reported 38.8%, Kang et al 17 who reported 28.8%, Jung et al18 who also reported 26% prevalence of AITD among T1DM patients and also with Perros et al19 who reported 31.4% as an incidence of thyroid dysfunction among T1DM female patients, but our results were lower than the study done by Heba et al20 , who found it 65%, while it is more higher than the study of Hansen et al 21 who found 5% of patients with T1DM had thyroid dysfunction.…”
contrasting
confidence: 60%